How dual value chain embedding affects energy efficiency in China - Chen, Guo; Cheng, Shixiong; Gao, Qizheng; Li, Baoxi (Frontiers in Environmental Science, 2022)
Since the financial crisis, especially after the outbreak of COVID-19, the global trade division of labor has been changing rapidly. The global value chain (GVC) keeps shrinking while the domestic value chain (DVC) continues to develop. Therefore, it is important to re-examine the impact of different modes of value chain division of labor on China’s energy efficiency. In this study, we first constructed an input-output model of provinces embedded in the world to measure the dual embedding of domestic and global value chains. Then we used a three-dimensional fixed-effect model to study the impact and mechanism of dual value chain embedding on energy efficiency. We found that domestic value chain embedding inhibits energy efficiency improvement and global value chain embedding promotes energy efficiency improvement. A series of robustness and endogeneity tests support these findings. The heterogeneity tests revealed that the effects of dual value chain embedding on energy efficiency are more pronounced in low-polluting industries, high-tech industries, years before 2008, and coastal regions. The mechanism test revealed that DVC embedding inhibits energy efficiency by exacerbating the low-end lock-in effect, reducing environmental regulation and scale efficiency, and it increases energy efficiency by increasing technological progress efficiency. GVC embedding improves energy efficiency by weakening the low-end lock-in effect and increasing technical efficiency and scale efficiency, and it inhibits energy efficiency improvement by reducing environmental regulation and technological progress efficiency.